Transformational sales leadership : sales leader perspectives - Eastman, C. A. (Christine A.) (Abingdon, Oxon ; New York, NY : Routledge, 2024)
Transformational Sales Leadership: Sales Leader Perspectives offers viewpoints from 12 leaders across the global sales industry, all of which challenge conventional sales models and promote visionary ways of thinking about sales and leadership. The leaders who share their professional stories in the book are from organizations including SAP, Google, Nationwide US, and Royal Caribbean, as well as their own practices, and they represent a new breed of salespeople who are increasingly sought after by organizations which need to transform their practices. They run teams, drive analytics, and improve operational excellence, and their careers rise or fall on getting the right KPIs. Their stories address solutions to age-old sales problems, but they bring a new perspective to the sales function in the digital age. The book focuses on what sales leaders need in order to be innovative. Specifically, the book shows you how to: Coach sales people through disruption Leverage the most valuable habits for success; and Provide for meaning and purpose in the hyper-connected and volatile sales industry If you are a sales professional looking to succeed in challenging scenarios, the journeys recounted in this book demonstrate how the landscape of sales has changed and how thinking about sales differently can help you transform your career.
Keywords: Sales management; Leadership; Selling; BUSINESS & ECONOMICS / Sales & Selling; BUSINESS & ECONOMICS / Strategic Planning